2015
DOI: 10.1109/tste.2015.2410760
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility Envelopes for Power System Operational Planning

Abstract: Operational planning is an integral part of maintaining economic operation of the bulk power system and keeping the lights on. Traditionally, power systems have been designed without ramping capability concerns, such that operational planning needed only focus on capacity adequacy, while assuming sufficient ramping capability. Today, the integration of renewable energy sources has led to increased variability and uncertainty in the power balance, thus warranting the need to carefully assess the ramping adequac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
102
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(102 citation statements)
references
References 61 publications
0
102
0
Order By: Relevance
“…Flying brick and probability box methods in [20] and [21], respectively, compute robust envelopes that enclose the net load with a specified probability level. The recent extension of these methods called flexibility envelopes was suggested in [22]. These envelopes are based on the same principles but evolve in time to respect the temporal evolution of reserve requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Flying brick and probability box methods in [20] and [21], respectively, compute robust envelopes that enclose the net load with a specified probability level. The recent extension of these methods called flexibility envelopes was suggested in [22]. These envelopes are based on the same principles but evolve in time to respect the temporal evolution of reserve requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the metrics of power provision capacity, power ramp-rate capacity, and energy provision capacity, a flexibility cube [35] is constructed for quantifying and visualizing the technically available operational flexibility. The flexibility envelop concept follows the same line but considers the time-evolution of reserve requirements, which resembles the shape of an envelope or a cone [36]. The flexibility envelope concept is extended by characterizing operating reserve dynamically in [37].…”
Section: Power System Operationmentioning
confidence: 99%
“…In the process of introducing VG into the power grid, many studies have demonstrated the lack of flexibility in the operation and planning of the system because unexpected variations in VG would lead to a power mismatch [4][5][6][7][8]. Flexibility is generally defined as the ability to respond to changes in net load (i.e., load minus VG).…”
Section: Introductionmentioning
confidence: 99%